Expression patterns of maize PIP aquaporins in middle or upper leaves correlate with their different physiological responses to drought and mycorrhiza - Paluch-Lubawa, Ewelina; Prosicka, Barbara; Polcyn, Władysław (Frontiers in Plant Science, 2022)
Here we report the effect of Rhizophagus irregularis on maize leaf expression of six plasma membrane aquaporin isoforms from PIP1 and PIP2 subfamilies under severe drought development and recovery. The novelty of our study is the finding that leaf-specific mycorrhizal regulation of aquaporins is dependent on the position of the leaf shoot and changes in parallel with the rate of photosynthesis and the stomatal response to drought. The transcripts were isolated from the upper third (L3) or ear (L5) leaf, which differed greatly in physiological response to stress within each symbiotic variant. Aquaporins expression in upper L3 leaves appeared to be largely not sensitive to drought, regardless of symbiotic status. In contrast, L5 leaf of non-mycorrhizal plants, showed strong down-regulation of all PIPs. Mycorrhiza, however, protected L5 leaf from such limitation, which under maximal stress was manifested by 6-fold and circa 4-fold higher transcripts level for PIP1s and PIP2s, respectively. Distinct expression patterns of L3 and L5 leaves corresponded to differences in key parameters of leaf homeostasis - stomatal conductance, photosynthetic rates, and accumulation of ABA and SA as phytohormonal indicators of drought stress. In result symbiotic plants showed faster restoration of photosynthetic capability, regardless of leaf position, which we recognize as the hallmark of better stress tolerance. In summary, arbuscular mycorrhiza alleviates short-term drought effects on maize by preventing the down-regulation of plasma membrane aquaporins within middle leaves, thereby affecting stomatal conductance.